Experimental Therapeutic Approaches for the Treatment of Retinal Pathology in Neuronal Ceroid Lipofuscinoses - Bartsch, Udo; Storch, Stephan (Frontiers in Neurology, 2022)
The neuronal ceroid lipofuscinoses (NCLs) are a group of childhood-onset neurodegenerative lysosomal storage disorders mainly affecting the brain and the retina. In the NCLs disease-causing mutations in 13 different ceroid lipofuscinoses genes have been identified. The clinical symptoms include seizures, progressive neurological decline, deterioration of motor and language skills and dementia resulting in premature death. In addition, deterioration and loss of vision caused by progressive retinal degeneration are major hallmarks of NCLs. To date there is no curative therapy for the treatment of vision loss. Key findings of different experimental approaches in NCL animal models aimed at attenuating progressive retinal degeneration and the decline in retinal function are discussed. Experimental enzyme replacement therapy, gene therapy, cell-based therapy and immunomodulation therapy were evaluated and showed encouraging therapeutic benefits. Recent experimental ocular gene therapies in NCL animal models with soluble lysosomal enzyme and transmembrane protein deficiencies have shown the strong potential of gene-based approaches to treat retinal dystrophies in NCLs. In CLN3 and CLN6 mouse models, an adeno-associated virus vector-mediated delivery of CLN3 and CLN6 to bipolar cells has been shown to attenuate retinal dysfunction. Therapeutic benefits of ocular enzyme replacement therapies were evaluated in CLN2 and CLN10 animal models. Since brain-targeted gene or enzyme replacement therapies will most likely not attenuate retinal neurodegeneration, treatment options additionally targeting the retina in NCL patients are needed. The benefits of these therapeutic interventions aimed at attenuating retinal degeneration and vision loss in NCL patients remain to be investigated in future clinical studies.